Mysteries of Mind and Matter in the Perspective of Colin McGinn’s Philosophy - Sepetyi, Dmytro; Сепетий, Дмитро Петрович (My University, 2016)
The paper discusses the approach to the mind-body problem that was developed by Colin McGinn and is known as “mysterianism”. The basic thesis of this approach, which McGinn opposes to both materialism and dualism, is that consciousness and its relationship to physical reality is an inscrutable mystery that cannot be get over in principle, because of insurmountable, constitutive limitations of human mind. In this paper, the critical analysis of McGinn’s approach is given. It is pointed out that McGinn’s thesis of the inscrutablility of the mind-body relationship is based on the ungrounded idea that a mediating substance is necessary. An argument is made that the mind-body relationship is better understood as interaction that is mediated only by natural psychophysical laws. McGinn’s hypothesis of the origin of physical space in a non-spatial reality that has the same nature as consciousness is explained in the context of different interpretations of the Big Bang theory. It is argued that McGinn’s hypothesis does not provide a solution to the problem of the origin of human consciousness, because consciousness belongs to mental individuals whose emergence is just as unexplainable by the hypothesis of non-spatial reality as it is by physical processes.
Keywords: philosophy; mind; matter; consciousness; mysterianism; dualism; uncognizable; non-spatial